STILESIA CAPRAI N. SP. FROM CAPRA HIRCUS (GOAT) AT SURPUR (KARNATAKA) INDIA - PATIL, D. P.; MIENKUNDLE, D. V. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2002)
The present communication deals with a study of Stilesia caprain.sp. The scolex of Stilesia caprai n.sp. is medium, globular, marked off from Strobila; Suckers large, oval occupying major portion of the scolex. Mature segments are small, squarish, transversely elongated, broader than long. Testes medium, oval situated in two lateral fields, 8 - 9 in numbers. Cirrus pouch medium, oval, cirrus is thin Stout, straight, curved. Ovary medium, Oval single mass with slightly irregular margin; ootype small, round, situated venterolateral to the ovary. Genital atrium large, oval, marginal; genital pores medium, Oval, presence of excretory canals in segment run laterally.